Motivational Implications of Heritage Language Identity for Heritage Language Learning - Berardi-Wiltshire, Arianna (Widya Mandala Catholic University Surabaya, 2013)
The article discusses the significance of elements of Italian identity (Italianità) for the language learning motivation of learners of Italian descent studying their heritage language (HL) by means of foreign language (FL) courses in Wellington, New Zealand. Adopting a social constructivist perspective on both second language learning and the motivational processes underlying it, the study utilizes qualitative data collected through waves of semi-structured interviews from five case-study participants to map the influence that their constructions of Italianità exert on their motivational trajectories over the course of several months of learning. The paper discusses a selection of data excerpts to show how motivational fluctuations are the result of the learners’ own processing of and reaction to elements of their sociocultural context. In particular, an analysis of the learners’ accounts of social exchanges and other crucial events involving the use of the HL outside the classroom will illustrate how these can support motivation by reinforcing the learners’ perceptions of their Italianità, strengthening existing learning goals and/or prompting the formation of new ones. The article concludes with some remarks on the implications for teaching practices and extra-curricular activities that could benefit HL learners by increasing their exposure to the HL outside the classroom while validating and encouraging the personal identity constructions and ambitions at the basis of their learning.